The Victory of the Islamic Party in the Christian Region Study: The Victory of the Partai Kebangkitan Bangsa in Samosir Regency in the 2024 General Election - Batubara, Putri Evi Ovi Yanti; Situmorang , Tonny P.; Kusmanto, Heri (Universitas Medan Area, 2025)
The 2024 election in Samosir Regency shows significant political changes with the victory of the National Awakening Party (PKB), which shifted PDI's dominance in Christian-majority areas. This study analyzes the factors that affect the success of PKB and the political strategies applied to gain support. Data was collected through interviews, observations, and document analysis using a descriptive qualitative method. The results of the study show that the PKB's victory in Samosir was influenced by several primary factors, namely political communication strategies based on pluralism and tolerance, the role of social networks and kinship (familyism), political migration from PDIP to other parties, and the weakening of PDIP's appeal due to internal divisions and negative campaigns. In addition, PKB has succeeded in adjusting its political narrative by prioritizing economic development and social welfare programs relevant to the people of Samosir. The success of a party in local politics is determined not only by ideology or money politics but also by community strategies, social recognition, and effective communication. In the future, PKB must maintain public trust by realizing work programs and ensuring political stability in Samosir.